2019
DOI: 10.11158/saa.24.11.10
|View full text |Cite
|
Sign up to set email alerts
|

<p class="Body"><strong>A new species of <em>Brevipalpus </em>(Acari: Tenuipalpidae) from the Azores Islands, with remarks on the <em>B.</em></strong><strong> </strong><strong>cuneatus species group</strong></p>

Abstract: Brevipalpus contains about 290 species, some of which are considered of economic importance. In spite of their agricultural importance, the species diversity is scarcely known in several regions around the world, notably on wild plants. In this work a new species collected on an endemic ivy of the Azores Archipelago, Hedera azorica Carrière (Araliaceae), is described based on an integrative approach using morphological traits of the adults, obtained through electron and light microscopy, and molecular characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
1
1
0
2
Order By: Relevance
“…Di Palma et al (2020) investigated its ultrastructural morphology in five Brevipalpus species (B. californicus, B. obovatus, B. papayensis, Brevipalpus tuberellus De Leon, and B. yothersi). They confirmed that the shape of the seminal receptacle is species-specific, stressing thus its importance as a key feature in Brevipalpus taxonomy and systematics, as it was previously suggested (Beard et al 2012(Beard et al , 2015Navia et al 2013;Alves et al 2019), and that females belonging to the same species and population may exhibit developed or undeveloped seminal receptacles. They also wondered whether those differences in the level of development can be attributed to environmental factors, physiological conditions or the age of females.…”
Section: Sex-ratio and Development Of Female Spermathecal Systemsupporting
confidence: 75%
“…Di Palma et al (2020) investigated its ultrastructural morphology in five Brevipalpus species (B. californicus, B. obovatus, B. papayensis, Brevipalpus tuberellus De Leon, and B. yothersi). They confirmed that the shape of the seminal receptacle is species-specific, stressing thus its importance as a key feature in Brevipalpus taxonomy and systematics, as it was previously suggested (Beard et al 2012(Beard et al , 2015Navia et al 2013;Alves et al 2019), and that females belonging to the same species and population may exhibit developed or undeveloped seminal receptacles. They also wondered whether those differences in the level of development can be attributed to environmental factors, physiological conditions or the age of females.…”
Section: Sex-ratio and Development Of Female Spermathecal Systemsupporting
confidence: 75%
“…Records in Bahia. Alves et al 2019 Remarks. All the specimens of B. tuberellus included in the molecular phylogenetic analysis of Alves et al (2019) and identified in the present study were collected from the municipality of Ilhéus by Kaélem S. Sousa.…”
Section: Brevipalpus Tuberellus De Leon 1960mentioning
confidence: 99%
“…Recognition of Brevipalpus species is difficult due to large intraspecies morphological variations Dos Santos Alves et al, 2019). Recent studies have revealed inconsistencies between the conventional morphological descriptions used for the mite classification and the molecular-based phylogenetic characterization based on molecular markers of the mitochondrial DNA cytochrome oxidase I (COI) gene, and even further, they have discovered the presence of cryptic species .…”
Section: Biology Diversity and Taxonomy Of Brevipalpus Mitesmentioning
confidence: 99%